2018
DOI: 10.1021/acs.joc.7b02846
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Halide Binding to a Neutral Bambusuril in Water and Organic Solvents

Abstract: Driving forces of anion binding in water in contrast to nonpolar environments are of high interest because of their relevance to biology and medicine. Here we report a neutral bambusuril macrocycle (1), soluble in both water and nonpolar solvents due to decoration with 12 polyethylene glycol-based substituents. The new bambusuril has the highest affinity for I in pure water ever reported for a synthetic macrocycle relying on hydrogen bonding interactions rather than metal coordination or Coulombic forces. Isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 57 publications
3
57
0
Order By: Relevance
“…It was reported that carboxyalkyl bambusurils complexes of HSO 4 − can be converted to their corresponding anion‐free BU[6] by a treatment with basic water . More recently (trioxadecyl) 12 BU[6], bearing polyethylene glycol substituents and TBABF 4 , was obtained as its NaBF 4 complex after purification by silicagel chromatography, and was obtained free of BF 4 − anion by water continuous extraction over one week . All these reported methods are burdensome and time consuming.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…It was reported that carboxyalkyl bambusurils complexes of HSO 4 − can be converted to their corresponding anion‐free BU[6] by a treatment with basic water . More recently (trioxadecyl) 12 BU[6], bearing polyethylene glycol substituents and TBABF 4 , was obtained as its NaBF 4 complex after purification by silicagel chromatography, and was obtained free of BF 4 − anion by water continuous extraction over one week . All these reported methods are burdensome and time consuming.…”
Section: Resultssupporting
confidence: 91%
“…Nitrobenzyl BU[4] derivatives have been successfully reduced into water‐soluble aminobenzyl BU[4] that were further transformed into the corresponding urea bambus[4]urils . Bambus[6]urils containing 12 (ethylene glycol) functions were recently reported to be as soluble in water as in nonpolar solvents . Although thiobambusurils are still unknown, some heterobambusurils called semithiobambus[4]urils and semithiobambus[6]urils have been prepared from semi‐thioglycoluril derivatives, and used as precursors for semi‐aza‐bambusurils bearing guanidines, which can act as anion channels .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon binding between I − and 1.Te , the released CD 3 CN molecules undergo a greater extent of re‐ordering compared with [D 6 ]acetone, giving rise to a greater entropic penalty. A similar reasoning has been invoked to account for the exothermic, but entropically disfavoured anion binding in solvents exhibiting a degree of structural ordering such as water and chloroform …”
Section: Resultsmentioning
confidence: 95%